Hierarchical NiCo-LDH core/shell homostructural electrodes with MOF-derived shell for electrochemical energy storage - Zheng, Kun (2022)
Constructing hierarchical structure is an effective strategy to boost the electrochemical performance of layered double hydroxide (LDH) materials, but the rational design of such delicate architectures is still challenging. Herein, a unique hierarchical core/shell homostructure with NiCo-LDH nanorods (NCNRs) as core and NiCo-LDH nanosheets (NCNSs) as shell is constructed via in-situ ZIF shell growth and subsequent ion exchange-coprecipitation process. Such novel hierarchical structure provides a large accessible surface area and more exposed electrochemical active sites. The in-situ growth and conversion process contribute to the formation of robust adhesion between the core and the shell, which could facilitate the effective charge and ion diffusion, as well as improve the mechanical stability. Benefiting from the unique structure, the NCNRs@NCNSs electrode exhibits a high capacitance of 2640.2 F g-1, along with the good rate performance and cyclic stability. Furthermore, the as-assembled asymmetric supercapacitor of NCNRs@NCNSs//AC device displays a high energy density of 22.81 Wh kg-1 at the power density of 374.95 W kg-1. This work demonstrates a new strategy for designing hierarchical LDH with core/shell structure as electrode materials for superior electrochemical energy storage.